KARAKTERISTIK PENGUJIAN TEGANGAN TEMBUS BOLAK-BALIK MINYAK WIJEN DENGAN MENGGUNAKAN ELEKTRODA HOMOGEN DAN TIDAK HOMOGEN - Haidar, Achmad; Dhofir, Moch.; Wibawa, Unggul (Jurnal Mahasiswa TEUB, 2024)
In the electric power transmission system from the generation to the consumers, a reliable system is needed. The transformer isone of the very important electrical components in this system. In high-voltage equipment, especially power transformers,insulation is essential to separate two or more high-voltage conductors. Transformer oil is one of the liquid insulating materialsthat serves as insulation and coolant in transformers. Failure of the insulation system in electrical equipment can result in abreakdown voltage that can occur in the liquid dielectric in the form of oil. Therefore, this research will describe the influenceof water content and electrode shape on the probability of breakdown voltage in the dielectric oil, specifically pure sesame oil,using an Alternating Current (AC) voltage source. The shape of the electrode will affect the distribution of the electric field inthe conductor within the power transformer. Non-uniform field distribution will increase the potential for breakdown voltage.The testing was conducted at the High Voltage and Application Laboratory, Department of Electrical Engineering, Faculty ofEngineering, Brawijaya University. The simulation of electric field distribution for each electrode shape was carried out usingFEMM 4.2 software. Purification through heating was done to reduce the water content in pure sesame oil. Electrical testing(breakdown voltage testing circuit) and physical testing (water content testing using the oven method) were conducted todetermine the feasibility of sesame oil as an insulator. The test results showed that the breakdown voltage value of pure sesameoil increased from 16.73 kV/2.5 mm to 38.54 kV/2.5 mm for plate-plate electrodes and from 14.03 kV/2.5 mm to 31.27 kV/2.5 mmfor needle-plate electrodes. Heating pure sesame oil at varying temperatures of 25-70°C for 15 minutes resulted in an increasein breakdown voltage, with the highest average at 70°C being 46.71 kV/2.5 mm for plate-plate electrodes and 38.46 kV/2.5 mmfor needle-plate electrodes. The uniformity of the electric field with plate-plate electrode shape was 1 or 100%, while for theneedle-plate electrode shape, it was 0.4785 or 47.85%. Keywords: Breakdown voltage, electric field, insulating oil, sesame oil, water content.